The Attitudes of European Medical Students towards the Clinical Importance of Neuroanatomy - Moxham, Bernard John; Brenner, Erich; Plaisant, Odile; Pais, Diogo; Stabile, Isabel; Scholz, Michael; Paulsen, Friedrich; Bueno-Lopez, Jose Luis; Reblet, Concepcion; Arraez-Aybar, Luis-Alfonso; Sotgiu, Maria Alessandra; Arsic, Stojanka; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2022)
The attitudes of medical students towards the clinical importance of neuroanatomy have been little studied. Because it has been reported that medical students find neuroanatomy difficult and can have 'neurophobia', here we test the hypothesis that early-stage medical students across Europe have a low regard for neuroanatomy's clinical relevance. The work was conducted under the auspices of the Trans-European Pedagogic Research Group (TEPARG), with just over 1,500 students from 12 European medical schools providing responses to a survey (52% response rate) that assessed their attitudes using Thurstone and Chave methodologies. Regardless of the university surveyed, and of the teaching methods employed for neuroanatomy, our findings were not consistent with our hypothesis. However, the students had a less favourable opinion of neuroanatomy's importance compared to gross anatomy; although their attitudes were more positive than previously reported for histology and embryology. The extent to which neuroanatomy plays a significant role in the early years of medical education is moot. Nevertheless, we conclude that in addition to newly recruited medical students being informed of the subject's role in a healthcare profession, we advocate the use of modern imaging technologies to enhance student understanding and motivation and cognisance of the core syllabus for the subject being developed by the International Federation of Associations of Anatomists (IFAA).
CRIS-Team WoS Importer:2021-10-29